Assessing Responsiveness of Elevated Serum Ferritin Levels for Treatment in Patients with Chronic Hepatitis C Infection - Waseem Ullah, Bushra Adeel, Anil Iqbal, Muhammad Ayyaz, Imran Joher, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The infection of HCV is recognized worldwide as an important community health problem. There is an optimistic correlation between accumulation of iron in hepatocytes and amplified serum levels of markers, counting ferritin and transferrin. Aim: The goal of this study is to determine the response of serum levels of ferritin after the patient’s treatment with HCV infection. Material and methods: The study included 140 HCV-infected patients. All subjects were evaluated for clinical topographies, including HCV viral load, status of serum iron levels and biochemical data. The obtained outcomes were calculated by means of Microsoft Excel 2013. Results: The results showed that treatment with antiviral drugs interfered significantly the iron deposition in hepatocytes and have association between iron accumulation and HCV treatment. The mean iron value was 20.02 µmol / L for the positive PCR patients; and for a negative PCR reaction, 25.11 µmol / L was the estimated value before treatment. Both values were lower the normal array of 9-31.3 µmol / L. It is estimated that the mean ferritin value for negative PCR (668.55 µmol / L) and positive PCR (913.14 µmol / L) is above normal range which is 221 to 641.35 µmol / L. Conclusions: Patients with chronic HCV are significantly related to serum iron levels. High levels of iron and ferritin were associated significantly with the disease, resulting progressive fibrosis in the liver. There is no considerable change in serum iron markers among subjects with increased or less severity of HCV infection. The severity of the disease can be evaluated easily by measuring the serum transferrin levels along with ferritin levels, which are linked with the progression of fibrosis of the liver and necro-inflammatory activity. Keywords: levels of serum ferritin; iron load; drug; liver cells and HCV infection.